Limnological Condition of Akap Reservoir, PayungSekaki District, Pekanbaru Basedon Physical and Chemical Parameters - Mandasari, Ayu Defi; Simarmata, Asmika Harnalin; Siagian, Madju (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTAKAP Reservoir was built to store excess water during the rainy season and as a recreation destination. A research aims to understand the limnological condition in the AKAP Reservoir based on physical-chemical parameters was conducted from March-April 2018. There were 4 sampling stations, namely Station 1 (inlet), Station 2 (in the middle of reservoir), Station 3 (in the middle of reservoir) and Station 4 (outlet). The water samples were taken once/week for a 3 weeks period. Water quality parameters measured were temperature, transparency, velocity, depth, water inflow, water level, pH, DO, CO2 free, nitrate and phosphate concentration. Results shown that the temperature was 29-300C, transparency 25.7-30.33 cm, depth 1.63-2.53 m, velocity 0.79-1.1 m/s, water inflow 0.26-0.31 m3/s, water level 86.3-116.7 cm, pH 5, DO 2.94-3.27 mg/L, CO2 free 7.99-11.98 mg/L, nitrate 0.04-005 mg/L, phosphate 0.06-0.09 mg/L. Based on the nitrate and phosphate concentrations, AKAP Reservoir can be categorized  as oligotrophic-mesotrophic.Keywords : AKAP Reservoir, Water Quality, Oligotrophic, Mesotrophic